Analysis of Reading Ability, Drafting Skills and Students' Complaints on Engineering Drawing of Grade XI of Machining Study Program - Yondi Akhiruddin; Subiyono Subiyono (Jurnal Dinamika Vokasional Teknik Mesin, 2017)
This study aims to determine and describe students' reading ability and drafting skills on technical drawing, and the students' complaints of school factors, which affect the learning process on engineering drawing subject in grade XI of Machining study program. This is a descriptive research with a quantitative approach. The population in this research were 112 students. The samples of 91 students were chosen using simple random sampling technique. Data were collected by means of tests and questionnaire. Data were then analyzed using descriptive analysis. The result shows that students' reading ability of engineering drawing is in the category of "high" with percentages of completion from the "comply with the drawing standard" indicator is 91.21% and "correctness" indicator is 40%.  Students' drafting skills is in the category of "high" with percentages of completion from the indicators of "comply with the drawing standard" is 79.12%, "clear and easy to understand" is 63%, "drafting speed" is 87%, and "cleanliness" is 89%. The most complained in terms of school factors on the subject of engineering drawing are student-teacher relationship, classroom equipment, building condition, and homework.Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan kemampuan siswa dalam membaca gambar, mengetahui dan mendeskripsikan kemampuan siswa dalam membuat gambar kerja, dan keluhan siswa ditinjau dari faktor sekolah yang mempengaruhi belajar mengajar siswa pada mata pelajaran gambar teknik kelas XI Teknik Pemesinan. Penelitian ini merupakan penelitian deskriptif kuantitatif. Populasi penelitian sebanyak 112 orang. Jumlah sampel sebanyak 91 siswa ditentukan dengan teknik simple random sampling. Data dikumpulkan dengan tes dan angket. Analisis data dilakukan dengan analisis deskriptif. Hasil penelitian menunjukan bahwa kemampuan siswa dalam membaca gambar berada pada kategori tinggi dengan presentase keberhasilan indikator tiap evaluasi pada standar sebesar 91.21% dan betul sebesar 40%, kemampuan siswa dalam membuat gambar berada pada kategori tinggi dengan presentase keberhasilan indikator tiap evaluasi pada standar sebesar 79.12%, jelas dan mudah dipahami sebesar 63%, kecepatan sebesar 87%, dan kebersihan sebesar 89%, dan keluhan siswa pada mata pelajaran gambar teknik ditinjau dari faktor sekolah yang cukup dikeluhkan adalah relasi guru dengan siswa, alat pelajaran, keadaan gedung, dan tugas rumah.